Genome Instability and Senescence Are Markers of Cornelia de Lange Syndrome Cells - Maddalena Di Nardo; Ian D. Krantz; Antonio Musio (Cells)
Cornelia de Lange syndrome (CdLS) is a rare, dominantly inherited multisystem developmental disorder. Pathogenic variants in genes encoding the structural subunits and regulatory proteins of the cohesin complex (NIPBL, SMC1A, SMC3, HDAC8, and RAD21) are the primary contributors to the pathogenesis of CdLS. Pathogenic variations in these genes disrupt normal cohesin function, leading to the syndrome’s diverse and complex clinical presentation. In this study, we discovered that cells harboring variants in the NIPBL, SMC1A and HDAC8 genes exhibit spontaneous genome instability, elevated oxidative stress and premature cellular aging. These findings suggest that cohesin plays a critical role in maintaining proper cellular function and highlight its contribution to the pathophysiology seen in the related diagnoses.